صلاحيات رئيس المجلس الشعبي البلدي في مجال البناء والتعمير - جرار حسين - كوسة عمار : (جامعة المسيلة, 2021)
تتجسد صلاحيات رئيس المجلس الشعبي في مجال البناء والتعمير، من خلال وضع الإطار والمرجع العام لأي لثمتي يذلا ،يلحملا ىوتسملا ىلع ينارمع طاشنأساسا في إ عداد أدوات التهيئة والتعمير، المكرسة في المخطط التوجيهي للتهيئة والتعمير، وكذا مخطط شغل الأراضي، كما لرئيس المجلس الشعبي البلدي في نفس إطار ممارسة هذه الصلاحيات بسط رقابته على أ نم ةعومجم حنم يف هتيحلاص قيرط نع ةيلبق نوكت يتلا ةباقرلا هذه ،ءانبلا لاغشالرخص للاخ نم ةيدعب ةباقرلا كلذك نوكتو ،مدهلا ةصخرو ةئزجتلا ةصخرو ءانبلا ةصخر يف ةلثمتملا متابعته لمختلف الأطوار التي تمر بها أشغال البناء ، هذه الاخيرة التي تنتهي بمنح شهادة المطابقة، وله كذلك في نفس هذا الإطار منح شهادة التقسيم في حال قابلية العقار المبني للقسمة، وقد ينتج عن ممارسة هذه الرقابة، جملة من الاثار من بينها لجوء رئيس المجلس الشعبي البلدي إصدار قرار الهدم، في حال مخالفة التوجيهات و الشروط التي تفرضها رخصة البناء ، وهو ما يترتب عنه نشوء العديد من المنازعات القضائية التي تتوزع بين القضاء العادي وال.يرادلاا ءاضق كلمات مفتاحية : صلاحيات، رئيس المجلس الشعبي البلدي، البناء والتعمير، رخصة، شهادة. Abstract : The powers of the President of the People's Assembly are reflected in the field of building and reconstruction, through the development of the framework and general reference for any urban activity at the local level, which consist mainly on the preparation of development and reconstruction tools, dedicated to the orientation plan for development and reconstruction, as well as the land occupancy plan. The President of the People's Municipal Assembly, in the same framework of the exercise of these powers, can impose the control over construction works, which shall be before the procedure, through its validity of a range of authorization, consist on the الــــفهــــرس 106 building, the subdivision and the demolition authorizations. Hence, The control also can be after the construction by following up on the various phases of the construction works, the latter which ends with the granting of the certificate of conformity, and in the same context it may also grant the certificate of division in the event of the divisibility of the property. As a result, a number of effects result from this control, including the resort of the president of the people's municipal assembly to issue the demolition decision, in case of violation of the directives and conditions imposed by the building authorization. Thus, many judicial disputes can rise; that are divided between the ordinary judiciary and the administrative judiciary. Key words: powers, President of the People's Municipal Assembly, building and reconstruction, authorization, certificate.
Keywords: صلاحيات، رئيس المجلس الشعبي البلدي، البناء والتعمير، رخصة، شهادة